Study On Digitization In Hr Practices In Global World (Journal of Namibian Studies : History Politics Culture, 2023)
Background: This study explores the use of digitization on HR practices in a global context. The transformation of HR in response to digitization is a critical aspect of organizational adaptation to the digital age.Method: A quantitative survey was conducted with 100 HR professionals. The survey included five questions to assess the level of HR digitization and the importance of digital transformation, and the preparedness of HR professionals.Findings: The findings indicate a diverse landscape of HR digitization, with varying levels of maturity. However key challenges in implementation include resistance to change and budget constraints. Notable digital strategies include HR analytics and automated recruitment systems. A strong consensus exists on the importance of digital transformation, and many HR professionals feel well-prepared for the digital age.